A comparative study of Ga2O3 nanowires grown on different substrates using CVD technique - Kumar, Sudheer; Tessarek, Christian; Christiansen, Silke; Singh, R. (Journal of Alloys and Compounds, 2014)
A comparative study of beta gallium oxide (β-Ga2O 3) nanowires (NWs) grown on different substrates such as silicon (Si), sapphire, and GaN/sapphire has been reported. Field emission scanning electron microscopy (FESEM) results revealed that the β-Ga 2O3 NWs grown on GaN/sapphire substrate were comparatively more aligned than grown on other substrates. The diameter of the NWs varied from 150 to 400 nm, and their length ranging up to tens of micrometers. X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM) showed the single crystalline monoclinic nature of NWs. The Raman spectra acquired from three samples revealed similar features consisting of two active modes such as mid and high frequency. However, low frequency mode was absent in our results. The cathodoluminescence (CL) spectra of β-Ga2O 3 NWs on different substrates showed a strong broad UV-blue emission band and a weak red emission band in all the samples. Hence, the morphologies and structural properties of the β-Ga2O3 NWs grown on three substrates showed some observable changes, while their optical properties were quite similar. © 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Cathodoluminescence; Gallium oxide nanowires; High resolution transmission electron microscopy; Raman spectra